2020
DOI: 10.1371/journal.pone.0239664
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity and prevalence of antibiotic resistance genes in the oral microbiome

Abstract: This study aims to describe the oral microbiome diversity and prevalence of ARGs in periodontal health and disease. Background The human oral cavity harbors a complex microbial community known as the oral microbiome. These organisms are regularly exposed to selective pressures, such as the usage of antibiotics, which drive evolution and acquisition of antibiotic resistance genes (ARGs). Resistance among oral bacteria jeopardizes not only antibiotic therapy for oral infections, but also extra-oral infections ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…For instance, Almeida et al . [148] reported significantly lower taxonomic diversity in subgingival microbial samples from both gingivitis and chronic periodontitis patients compared to healthy individuals (total of 110 participants). However, Griffen et al [150] reported a significantly higher taxonomic diversity for chronic periodontitis individuals compared to healthy controls (58 participants in total).…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 96%
See 1 more Smart Citation
“…For instance, Almeida et al . [148] reported significantly lower taxonomic diversity in subgingival microbial samples from both gingivitis and chronic periodontitis patients compared to healthy individuals (total of 110 participants). However, Griffen et al [150] reported a significantly higher taxonomic diversity for chronic periodontitis individuals compared to healthy controls (58 participants in total).…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 96%
“…In terms of periodontal disease, changes in microbial diversity remain controversial, with some reports indicating loss of microbial diversity with periodontitis [146] , [147] , [148] , [149] , and others indicating the opposite (i.e., that periodontitis is associated with increased levels of microbial diversity compared to healthy control levels; as a consequence of the increased amount of nutrients derived from host’s tissue degradation [135] , [139] , [140] , [149] , [150] , [151] ; and even others reporting no significant difference between the groups (i.e., periodontitis vs. healthy patients) [152] , [153] . For instance, Almeida et al .…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 99%
“…Previous studies analysed microbiome in the oral cavity of the patients suffering from periodontal diseases, but resistance genes except of bla TEM , bla CfxA and erm genes were not found (Almeida et al 2020;Arredondo et al 2020). The dominant species harbouring resistance determinants in sub gingival samples were Streptococcus spp and Prevotella spp, bacteria belonging to normal microbiota of the oral cavity.…”
Section: )mentioning
confidence: 86%
“…Antibiotics are suggested in the cases of prophylaxis for local and focal infections, besides, for the treatment of odontogenic and nonodontogenic infections [ 13 , 15 ]. Antibiotics are not indicated for all odontogenic infections; they should not be used instead of removal of the source of infections [ 16 ].…”
Section: Indications Of Antibioticsmentioning
confidence: 99%